Design and Efficient Synthesis of New 4-Amino-Substituted 2-(4-Bromobenzyl)-5,6,7,8-tetrahydrobenzo[4,5]thieno[2,3-d]pyrimidines of Anticancer Interest and Their In Silico Study - Arora, Sahil; Thakur, Shikha; Kaki, Venkata Rao; Kumar, Raj (Synthesis, 2024)
Thienopyrimidines are an emerging class of fused pyrimidines due to their broad spectrum of pharmacological properties, including antimicrobial, anti-inflammatory, antimalarial, anticancer, etc. The anticancer activity of these compounds has been mechanistically proven via the inhibition of validated drug targets, such as EGFR, VEGFR-2, PI3K, and c-kit. In this research article, we designed and synthesized new 4-amino-substituted 2-(4-bromobenzyl)-5,6,7,8-tetrahydrobenzo[4,5]thieno[2,3-d]pyrimidines to explore their anticancer potential. These heterocycles were designed based on pharmacophoric features of the core heterocycle, varying its C4 substitution with a variety of amines and considering cancer protein-ligand interactions with the aim to obtain potent lead molecules. The target compound-protein interaction complexes were analyzed, and lead compounds were identified based on their better binding affinity in molecular docking studies.
Keywords: thienopyrimidine; benzo[4,5]thieno[2,3-d]pyrimidines; microwave irradiation; anticancer; synthesis; molecular docking; ADME